Integrative Phytochemical and Computational Study of Curcuma aeruginosa as a Natural PI3K/AKT-1 Inhibitor Against HCC - Khairi, Elvina Rashida; Widyananda, Muhammad Hermawan; Dwijayanti, Dinia Rizqi; Annisa, Yuslinda; Ulfa, Siti Mariyah; Widodo, Nashi (Biotropika: Journal of Tropical Biology, 2026)
Curcuma aeruginosa RoxB., a medicinal plant known for its diverse pharmacological properties, has shown promising anticancer potential. In this context, the search for multitarget natural compounds remains a key strategy for developing safer and more effective therapies for hepatocellular carcinoma (HCC). Therefore, this study aimed to characterise the phytochemical composition of C. aeruginosa ethanolic extract and its fractions, and to investigate their potential molecular mechanisms against HCC through in silico approaches. Phytochemical quantification revealed that the ethanolic extract contained high levels of phenolic compounds, consistent with the LC-HRMS detection of phenol and phenylpropanoid derivatives. Conversely, the low total terpenoid content may be due to the use of linalool as a single standard, as the LC-HRMS results indicated abundant terpenoid constituents. Drug-likeness and bioactivity screening of the identified compounds revealed eight candidates with potential anticancer properties, including PTOX, 4’-demethylepipodophyllotoxin, dehydrocostus lactone, tretinoin, and vitamin A. Network and molecular docking analysis indicated that these compounds primarily target proteins involved in apoptosis and cancer-related pathways, particularly PI3K and AKT1. Molecular dynamics simulations confirmed the stability of the selected protein-ligand complexes, with PTOX and 4’-demethylepipodophyllotoxin showing the most favourable interactions with both target proteins. Collectively, these findings highlight C. aeruginosa, especially its crude ethanol extract, as a potential source of multitarget natural inhibitors against PI3K and AKT1, supporting its potential role as a promising candidate for the development of natural-based anti-HCC agents.